Business Model Canvas Training to Improve Management Capacity of Salma Frozen Food MSMEs - Heirunissa; Sitanggang, Jhonson; Maulida, Siti Anshori; Octaviani, Siti Nurani; Oci, Siti Nur (ALMUJTAMAE: Jurnal Pengabdian Masyarakat, 2025)
The Business Model Canvas (BMC) is a strategic framework that enables MSMEs to holistically visualize, design, and test their business models. Although the BMC is widely recognized, its implementation among MSMEs is often hampered by limited understanding and resources. Therefore, this PKM activity focuses on how structured mentoring can bridge this gap. The partner was the owner of Roti Canai Ka Salma Frozen Food, using a participatory approach involving frozen food business owners in the target area. The methods used included an implementation workshop, socialization, and mentoring, which compared the management conditions of Ka Salma Frozen Food, including understanding market segments, value propositions, revenue streams, and cost structures, before and after mentoring. The results of the activity showed that partners who initially lacked understanding of business planning were now able to identify critical elements of BMC, manage resources, and develop marketing and product diversification strategies more effectively. The socialization and workshop on BMC implementation significantly improved the understanding and management capacity of MSMEs. Participants were able to identify and map their business elements more clearly, moving from a previously undirected to a more structured one. This improvement is not limited to theoretical aspects but is also evident in the ability of MSMEs to make strategic decisions, such as product diversification or more appropriate pricing. Thus, BMC training has proven to be an effective tool for empowering MSMEs to face business challenges and increase competitiveness.